The Prevalence of Osteoporosis in Hiv Infected Patient and its Correlation with Cd4 Count/Clinical Staging in Indian Population - Kant Tiwari Satya; Patel Richa (Journal of Clinical Research In HIV AIDS And Prevention, 2020)
Human immunodeficiency virus (HIV) is a retroviral disease in which the viruses copy their genetic material into the genetic material of the human beings. Infected cells remain infected for the whole of their life. First discovered in the year 1981, Human immunodeficiency virus infections is considered to be a pandemic by the World Health organization.
Keywords: Bone mineral density (BMD)